Manajemen Peningkatan Kinerja Pegawai Di Rskia Pku Muhammadiyah Kotagede - Munawara Salfitri; Ibnu Yanuar iswantoro (EKONOMI DAN BISNIS DIGITAL, 2023)
This study seeks to examine the management of employee performance improvement in the work environment. The purpose of this study is to find out how management improves employee performance, obstacles in improving employee performance, and how the hospital's efforts to overcome obstacles in managing employee performance improvement. The research method uses descriptive qualitative data sources in the form of primary data and secondary data. In which the data were obtained by observation, interviews and documentation, while the method of data analysis uses data analysis methods that use qualitative description data analysis. The results of this study are divided into 3 parts based on the first research hypothesis, namely employee performance, namely work quality, work quantity, task execution, and responsibility, and factors that influence employee performance, namely ability factors, and motivational factors. Furthermore, the second hypothesis of the leadership style that occurs is the autocratic leadership style. In an autocratic way of leading, decision making is usually only done by the leader himself. And the last is the third hypothesis which is to overcome obstacles in the management of improving employee performance, namely by providing refreshing and leadership style training.